Macrophages: their role in immunity and their relationship with fatty acids in health and disease - Rueda-Munguía, Mayte; Luévano-Martínez, Luis Alberto; García-Rivas, Gerardo; Castillo, Elena Cristina; Lozano, Omar (Frontiers in Immunology, 2025)
The intricate interplay between macrophage biology and lipid metabolism has emerged as a critical determinant of metabolic homeostasis, disease progression and pathogenesis. This comprehensive review explores the molecular mechanisms through which fatty acids activate macrophage function, emphasizing their selective engagement of pattern recognition receptors such as Toll-like receptors (TLRs), CD36, and GPR120. Notably, saturated fatty acids (SFAs) like lauric acid (C12:0) and palmitic acid (C16:0) activate TLR2 and TLR4 signaling pathways. Palmitic acid triggers mitochondrial dysfunction and lysosomal destabilization, leading to NLRP3 inflammasome activation and chronic low-grade inflammation. In contrast, ω-3 polyunsaturated fatty acids (PUFAs), such as docosahexaenoic acid, help resolve inflammation through GPR120-mediated signaling and the production of specialized pro-resolving mediators (SPMs) like resolvins, protectins, and maresins. This review establishes a paradigm for understanding the complex relationship between dietary lipids, innate immunity, and metabolic health, with broad implications for immunometabolic interventions.